Perancangan Sistem Informasi Manajemen Gudang Jamu Semar berbasis Web menggunakan Framework Laravel - Pratama Hendra Wijaya (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
In a business venture, it must have a lot of data such as available quantities, purchase prices, sale prices, and consumer and regular customer data. Located in the town of Tegal, it has a steady total of customers, and it is one of the best-known herbal businesses in the town of tegal. However, the application still USES sufficient manual transcription, which can easily lead to a loss of data. It is hoped that the management information system can assist in logging, starting with the consumer, the least, and the data of each herb bought in these Semar herbs. In the development of the information system, they use waterfall, and they apply the SDLC principles. The design implements software engineering so that in development for the development of this information system can be better. The conclusion of this study is that semiarar herbs casimilar structured information system, a neat, well-kept record for packaging, amounts, and availability of materials can be made even more systematic. As for the Suggestions of this research, it is expected that the next information system developer will be able to examine the flow of data, and the data stream and safety levels of this information system.